Utenforskap, stigmatisering og fremmedfrykt på Agder: 1860 til i dag - Vadum, Kristoffer; Homane Grødum, Kjetil; Olsen, Thomas; Seines, Anne Mette; Hagen, Thomas V. H.; Hundstad, Dag; Kurszus Håland, Monika; Hessaa-Szwinto, Solveig; Magnussen, May-Linda; Alasow, Mona; Haaland, Hanne; Wallevik, Hege (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2024)
The title of this anthology – Outsiders, Stimatization and Xenophobia in Agder: From 1860 to the Present – conveys a critical perspective on society’s treatment of those who deviate from accepted norms and expectations in Agder. It also takes a historical perspective on the search for solutions that balance consideration for individual autonomy and dignity with the need to maintain order, conformity and norms for participation in society.